Determinants of Tobacco Use among Adolescents and Young Adults in Indonesia: An Analysis of IFLS-5 Data - Diyan Effendi; Arief Priyo Nugroho; Zainul Khaqiqi Nantabah; Agung Dwi Laksono; Lestari Handayani (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background:The danger of tobacco use to health has been globally known. However, its prevalence especially in developing countries including Indonesia remains high.This study aims to investigate determinants of tobacco use among adolescents and young adults in Indonesia. These age groups are essential since most regular smokers initiated to smoke at these ages. Methods: This study utilized IFLS wave 5 data. A total of 7213 responses on tobacco use from respondents age 15-24 years old were taken into analysis. Association between tobacco use with sociodemographic, religious, and ethnic identity was determined by using binary logistic regression. Results: Prevalence of tobacco use was 25.1%. The fully adjusted model showed factors that associated with tobacco use were age, sex, educational attainment, marital status, having smoking parents, and Madurese ethnicity. Conclusion:Tobacco use was prevalent among adolescents and young adults in Indonesia. Madurese was the only ethnic group associated with tobacco consumption in Indonesia. Appropriate design of interventions, therefore, is needed to target these subgroups.